The Combining Ability of Glycoproteins IIb, IIIa and Ca2+ in EDTA-Treated Nonaggregable Platelets - Zucker, Marjorie B; Varon, David; Masiello, Nicholas C; Karpatkin, Simon (Thrombosis and Haemostasis, 1983)
Platelets deprived of calcium and incubated at 37° C for 10 min lose their ability to bind fibrinogen or aggregate with ADP when adequate concentrations of calcium are restored. Since the calcium complex of glycoproteins (GP) IIb and IIIa is the presumed receptor for fibrinogen, it seemed appropriate to examine the behavior of these glycoproteins in incubated non-aggregable platelets. No differences were noted in the electrophoretic pattern of nonaggregable EDTA-treated and aggregable control CaEDTA-treated platelets when SDS gels of Triton X- 114 fractions were stained with silver. GP IIb and IIIa were extracted from either nonaggregable EDTA-treated platelets or aggregable control platelets with calcium-Tris-Triton buffer and subjected to sucrose density gradient centrifugation or crossed immunoelectrophoresis. With both types of platelets, these glycoproteins formed a complex in the presence of calcium. If the glycoproteins were extracted with EDTA-Tris-Triton buffer, or if Triton-solubilized platelet membranes were incubated with EGTA at 37° C for 30 min, GP IIb and IIIa were unable to form a complex in the presence of calcium. We conclude that inability of extracted GP IIb and IIIa to combine in the presence of calcium is not responsible for the irreversible loss of aggregability that occurs when whole platelets are incubated with EDTA at 37° C.
Keywords: Platelet aggregation; Glycoproteins IIb and IIIa; EDTA